2010
DOI: 10.5194/acp-10-11489-2010
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fatty acid surfactants on the uptake of ozone to aqueous halogenide particles

Abstract: Abstract. The reactive uptake of ozone to deliquesced potassium iodide aerosol particles coated with linear saturated fatty acids (C 9 , C 12 , C 15 , C 18 and C 20 ) was studied. The experiments were performed in an aerosol flow tube at 293 K and atmospheric pressure. The uptake coefficient on pure deliquesced KI aerosol was γ = (1.10±0.20)×10 −2 at 72-75% relative humidity. In presence of organic coatings, the uptake coefficient decreased significantly for long straight chain surfactants (≥C 15 ), while it w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 67 publications
1
34
1
Order By: Relevance
“…There is excellent agreement in the retrieved parameters α b and k II of Rouvière et al (2010) and despite the different types of experiments. The liquid phase rate constant k II obtained in both studies agreed with literature values (Garland et al (1980) derive 2 × 10 9 M −1 s −1 at 298 K) and the values reported by are recommended.…”
Section: Comments On Preferred Valuesmentioning
confidence: 53%
See 4 more Smart Citations
“…There is excellent agreement in the retrieved parameters α b and k II of Rouvière et al (2010) and despite the different types of experiments. The liquid phase rate constant k II obtained in both studies agreed with literature values (Garland et al (1980) derive 2 × 10 9 M −1 s −1 at 298 K) and the values reported by are recommended.…”
Section: Comments On Preferred Valuesmentioning
confidence: 53%
“…Known bulk aqueous phase kinetics was unable to explain Cl 2 formation in the study by Knipping et al (2000) and later by Knipping and Dabdub (2002). Therefore, an Eley-Rideal type surface reaction was proposed to bring experiment and simulation into agreement, which is recommended in parameterized form as a function of the chloride concentration.…”
Section: Comments On Preferred Valuesmentioning
confidence: 99%
See 3 more Smart Citations